Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5114/wo.2016.61850
|View full text |Cite
|
Sign up to set email alerts
|

Total antioxidant status in lung cancer is associated with levels of endogenous antioxidants and disease stage rather than lifestyle factors – preliminary study

Abstract: Aim of the studyDecreased total antioxidant capacity (TAC) has been reported in different neoplasms, including lung cancer. However, no study concerning the relationship between endogenous antioxidants, lifestyle factors, and TAC has been conducted among lung cancer patients. The purpose of the study was to investigate the associations between endogenous antioxidants, severity of disease, lifestyle factors, and TAC in lung cancer patients.Material and methodsThe study was conducted among 59 lung cancer patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…In this study we demonstrated that lung cancer patients had significantly lower total antioxidant capacity compared to control subjects, regardless of circulating glucose concentrations, while parameters related directly to oxidative stress were increased only in patients with elevated glucose levels. However, in our previous study [ 5 ], similarly to this one ( S2 Table ), we found that depletion of the antioxidant defense system in lung cancer was not related to smoking status but rather disease progression. Therefore, we concluded that there are possible factors, other than smoking, which affect redox state in lung cancer.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In this study we demonstrated that lung cancer patients had significantly lower total antioxidant capacity compared to control subjects, regardless of circulating glucose concentrations, while parameters related directly to oxidative stress were increased only in patients with elevated glucose levels. However, in our previous study [ 5 ], similarly to this one ( S2 Table ), we found that depletion of the antioxidant defense system in lung cancer was not related to smoking status but rather disease progression. Therefore, we concluded that there are possible factors, other than smoking, which affect redox state in lung cancer.…”
Section: Discussionsupporting
confidence: 72%
“…In lung cancer, as well as in many other site-specific cancers, the redox status is altered and depletion of antioxidant capacity is observed along with tumor progression [ 1 5 ]. Several mechanisms may induce this perturbation, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Zabłocka-Słowińska et. al, uric acid level was found to be lower in smokers than in non-smokers (23). Further research is needed in primary care to determine if there is a clinically useful role of serum uric acid levels in risk stratification.…”
Section: Discussionmentioning
confidence: 95%
“…It has been confirmed that antioxidant/oxidant status changes in lung cancer, as well as in many other site-specific cancers, and a depletion of antioxidant capacity has been observed along with tumor progression. 27 Despite this, the mechanisms of redox disturbance in lung cancer patients are still not entirely clear. Cigarette smoking and lung inflammation, as well as systemic inflammation, are recognized as major causes of depletion of antioxidant Differences were assessed using the Mann-Whitney U test or Student's t-test between sex-related groups of lung cancer patients and control subjects; p < 0.05 (observed significant differences between compared groups are in bold); LW -lung cancer women; CW -control women; LM -lung cancer men; CM -control men; BMI -body mass index; FFMI -fat-free mass index; BFP -body fat percentage; WC -waist circumference; HC -hip circumference; WHR -waist-to-hip ratio; CC -calf circumference; MAC -mid-arm circumference.…”
Section: Discussionmentioning
confidence: 99%